Role of cadmium gallate nanoparticles on the cathode of microbial fuel cells for enhanced bioelectricity production - Sahni, Mohit; Kumar, Ankit; Gupta, Pankaj; Khan, Azmat Ali; Mathuriya, Abhilasha Singh; Pandit, Soumya; Sharma, Kuldeep; Roy, Amit; Ranjan, Nishant; Yahya, M.Z.A.; Noor, I.M. (Springer Science and Business Media Deutschland GmbH, 2024)
Bringing microbial fuel cells (MFCs) to market requires the use of non-precious metal catalysts. Therefore, we replaced the platinum (Pt) cathode with more cost-effective cadmium gallate (CdGa2O4) nanoparticles in the present research. The synthesis and characterization of cadmium gallate (CdGa2O4), and further its application as a cathode catalyst for oxygen reduction reaction (ORR) in a MFC. The physiochemical characterization indicates a high ORR property of CdGa2O4, attributed to the presence of active sites, high electronic conductivity, and high surface area. These features enhanced the bioelectricity production with simultaneous wastewater treatment which resulted into comparable performances to catalysts such as platinum (Pt). The electrochemical analysis shows that the loading rate of CdGa2O4 has a significant impact on the power output of the MFC. The highest volumetric power density was observed in CdGa2O4 with a loading of 1 mg/cm3 (8.2 W/m3). COD removal efficiency also showed a similar trend with respect to different loading rates. 1 mg/cm3 of CdGa2O4 showed the highest COD removal and Columbic efficiency of 83.8% and 11.7%, respectively. The low cost-to-performance ratio, high ORR activity, and high electric conductivity of CdGa2O4 prove that CdGa2O4 is a feasible substitute for Pt in large-scale operations of MFC.